Rites and rank : hierarchy in biblical representations of cult - Olyan, Saul M. (Princeton University Press, 2000)
Good and evil, clean and unclean, rich and poor, self and other. The nature and function of such binary oppositions have long intrigued scholars in such fields as philosophy, linguistics, classics, and anthropology. From the opening chapters of Genesis, in which God separates day from night, and Adam and Eve partake of the tree of the knowledge of good and evil, dyadic pairs proliferate throughout the Hebrew Bible. In this groundbreaking work melding critical exegesis and contemporary theory, Saul M. Olyan considers the prevalence of polarities in biblical discourse and expounds their signific.